Low-carbon transition and common prosperity: a quasi-natural experiment based on pilot policies of low-carbon cities - Liang, Jingyi; Qiao, Cuixia (Frontiers in Environmental Science, 2025)
IntroductionGreen and low-carbon development is a fundamental pathway to modernization and a critical driver of common prosperity. Using panel data from 279 prefecture-level cities in China from 2010 to 2022, this study empirically examines the impact of low-carbon city pilot policies on common prosperity and their underlying mechanisms.MethodsCommon prosperity is measured using principal component analysis, and a staggered difference-in-differences model is applied for empirical analysis. Robustness is verified through parallel trend test, placebo test, propensity score matching difference-in-differences, instrumental variable estimation, etc. Additionally, a moderation model is used to examine the U-shaped moderating effect of green technological innovation on the relationship between low-carbon transition and common prosperity.ResultsThe implementation of low-carbon city pilot policies significantly promotes common prosperity, this result remained robust in multiple robustness tests, and this effect exhibits a time lag. Green technological innovation plays a U-shaped moderating role in the relationship between low-carbon city pilot policies and common prosperity. Low-carbon city pilot policies contribute to common prosperity by enhancing employment quality and fostering human capital agglomeration. The positive effects of low-carbon city pilot policies are more significant in eastern and central regions, non-central cities, cities with lower urbanization levels, and cities with smaller income distribution gap.DiscussionBased on the findings, this study recommends advancing low-carbon city pilot policies through region-specific strategies, promoting green innovation and high-quality employment, and fostering human capital development through targeted support measures. Furthermore, it is essential to establish dynamic policy evaluation and adjustment mechanisms, while strengthening interregional cooperation and ensuring equitable labor mobility, to achieve the coordinated progress of urban green transformation and common prosperity.